PENYIDIKAN TINDAK PIDANA KORUPSI TERHADAP TNI OLEH PENYIDIK KPK - BAHRI YAMIN; FITRIANI AMALIA; SARUDI SARUDI; SAHRUL SAHRUL; FAHRURROZI FAHRURROZI (Universitas Mahasaraswati K. Mataram, 2023)
Regarding the polemic regarding the determination of suspects by KPK investigators against active TNI soldiers. The central point is the issue of authority. The authority in question is related to whether or not KPK investigators may carry out investigations and determine suspects against active TNI soldiers. So the researchers proposed a problem formulation; Does the Corruption Eradication Committee have the authority to investigate criminal acts of corruption committed by active TNI while holding civilian positions? The aim to be achieved with this legal issue is to find out and provide scientific information to interested parties. This research is a type of Normative legal research.